Clinical and Epidemiological Characteristics of Pediatric Pertussis Cases: A Retrospective Study from Southeast Romania - Cristina Maria Mihai; Ancuta Lupu; Tatiana Chisnoiu; Adriana Luminita Balasa; Ginel Baciu; Silvia Fotea; Vasile Valeriu Lupu; Violeta Popovici; Simona Claudia Cambrea; Mircea Grigorian; Felicia Suciu; Florin-Daniel Enache; et al. (Antibiotics)
Background/Objectives: Pertussis remains a significant cause of respiratory illness in children, particularly in regions with suboptimal vaccination coverage. This retrospective study analyzes the clinical presentations, co-infections, treatment, and outcomes of pediatric patients diagnosed with Bordetella pertussis at the Constanța County Clinical Emergency Hospital “St. Apostle Andrew” between 1 January and 30 September 2024. Methods: Thirty-eight children, predominantly under the age of 3 years (81.58%), were included. Demographic data, clinical features, coinfecting pathogens, antimicrobial regimens, and hospital outcomes were reviewed. Results: Only 7 out of 38 children (18.42%) had received pertussis vaccination, and none benefited from maternal immunization. The highest incidence occurred in infants under 1 year (44.74%). Intensive care was required in 18.42% of cases, and macrolides were the most frequently used antibiotics (68.42%). Co-detection of respiratory pathogens—particularly Streptococcus pneumoniae, enteroviruses, and human rhinoviruses—was common. Severe cases often exhibited hyperleukocytosis, which was associated with complications such as heart failure. Conclusions: These findings underscore the need for timely recognition and management of pertussis and its complications. Although macrolides remain the first-line therapy, adjunctive treatments like leukoreduction may be considered in critical cases. The persistence of pertussis despite vaccination efforts highlights the challenges posed by waning immunity and diagnostic limitations, reinforcing the need for strengthened public health strategies.